Does discrimination breed grievances—and do grievances breed violence? New evidence from an analysis of religious minorities in developing countries. (May 2017) - Basedau, Matthias; Fox, Jonathan; Pierskalla, Jan H.; Strüver, Georg; Vüllers, Johannes
Since Ted Gurr's Why Men Rebel it has become conventional wisdom that (relative) deprivation creates grievances and that these grievances in turn lead to intergroup violence. Recently, studies have yielded evidence that the exclusion of ethnic groups is a substantial conflict risk. From a theoretical angle, the relationship is straightforward and is likely to unfold as a causal chain that runs from objective discrimination to (subjective) grievances and then to violence. We test this proposition with unique group-format data on 433 religious minorities in the developing world from 1990 to 2008. While religious discrimination indeed increases the likelihood of grievances, neither grievances nor discrimination are connected to violence. This finding is supported by a large number of robustness checks. Conceptually, discrimination and grievances can take very different shapes and opportunity plays a much bigger role than any grievance-based approach expects.